The Antarctic Peninsula: Argentina and Chile in the era of global change - Vidal, Florian (The Polar Journal, 2023)
While Argentine-Chilean relations have long been swayed between cooperation and confrontation since their independence in the 19th century and a long-standing presence in Antarctica, the stretch between Tierra del Fuego to the Antarctic Peninsula stands as the closest lane (i.e. about 1,000 km) to any other continent. Despite their territorial dispute over islands on the fractured southern tip of South America and territorial claims on the Antarctic, their common diplo-matic ground successfully defuses any potential geopolitical instability. Along with Chile and Argentina, British claims overlap in the Antarctic Peninsula, which establishes unique geopolitical conditions in the whole of Antarctica. In this context, scientific missions and growing tourist activities could transform the region into the Antarctic gateway. From potential mineral resources exploitation to the United States- China global competition, the South Atlantic area could become a strategic bridgehead in light of the brewing geopolitical shift during the 21st century. Considering that climate change and geostrategic conditions evolve somewhat quickly to transform the Western Antarctic area, this article aims to assess and comprehend how these external drivers may affect the two South American countries. Given the fact that Antarctica is part of their respective national narrative, how do Argentina and Chile intend to maintain their presence and protect their interest in these shifting conditions? What are the vectors for partnering with the world’s great powers, such as China? Ultimately, could this space become a choke point through the 21st century?
Keywords: Antarktis; geopolitikk; politikk; ressurser

Animals as instruments of Norwegian imperial authority in the interwar Arctic - Roberts, Peder; Jørgensen, Dolly (Journal for the History of Environment and Society, 2016)
During the first half of the twentieth century a number of individuals in Norway participated in the transfer of animals from both the Arctic to the Antarctic regions and vice versa. These projects may be conceptualized as a form of imperial acclimatization, following in the footsteps of earlier attempts to transplant both plants and animals from their indigenous ranges to new geographic locations for both practical and recreational purposes. Reindeer were introduced to the island of South Georgia before World War I as Norwegian whalers turned a space previously uninhabited by humans into the operational hub of a booming Antarctic whaling industry. The successful transplantation of reindeer was followed by less successful attempts to transfer muskoxen from Greenland to Svalbard and the Scandinavian mainland, penguins from the Antarctic to the coast of Norway, and dreams of transferring fur seals from south to north. We argue that these attempts constituted both practical attempts to “enrich” the fauna of discrete habitats, but also expressions of Norwegian authority over the polar regions at a time when imperial ambitions in both the Arctic and Antarctic had significant traction within Norway. The transplanted animals may thus be conceived as geopolitical instruments – mastery over fauna as being a means of expressing mastery over space.
Keywords: Antarktis; Bouvetøya; Norge; geopolitikk; hvalfangst; polarområdene

The ANTOSTRAT Legacy: Science Collaboration and International Transparency in Potential Marine Mineral Resource Exploitation of Antarctica - Cooper, Alan; Barker, Peter; Barrett, Peter; Behrendt, John; Brancolini, Giuliano; Childs, Jonathan; Escutia, Carlota; Jokat, Wilfried; Kristoffersen, Yngve; Leitchenkov, German; Stagg, Howard; Tanahashi, Manabu; et al. (Science Diplomacy: Antarctica, Science, and the Governance of International Spaces, 2011)
Keywords: Antarktis; geopolitikk; internasjonal samarbeid; marin geologi; mineraler; ressurser; stratigrafi; tektonikk